Secondary Borrowing of Lexical Units as Active Process in Modern Russian Language - Y. Yu. Mageramova (Научный диалог, 2019)
The relevance of the study is determined by the author’s appeal to the analysis of one of the dynamic processes that characterize the current state of the lexico-semantic system - secondary borrowing of foreign words. The questions concerning the differentiation of terminological words and phrases used by modern lexicologists in the process of studying the active processes occurring in the Russian language at the turn of the century are considered. Attention is paid to the analysis of approaches to foreign language vocabulary both “returned” from the passive lexicon and re-borrowed from foreign languages in the period of the late 20th - early 21st centuries. The question of expediency of use in a number of cases of the term secondary borrowing as the most accurately reflecting essence of the occurring processes is raised. Special attention is paid to the distinction between cases of dearchaization and secondary borrowing. The causes of vocabulary dearchaization are covered, among them being pro-western and pro-Russian tendencies inherent in modern social consciousness. Analysis of the tokens governor and bachelor proves, that the term dearchaizated (reactivated) vocabulary traditionally used in relation to certain words of lexical-thematic groups “Public-political organization” and “Education” should be replaced by the term secondary borrowed vocabulary .